Psychosocial factors as a predictor of academic achievement among student-athletes in a Malaysian sports school - Abdullah, Mohd Amirul Syafiq (2022)
Despite excelling in competitive sports, student-athletes have consistently underperformed academically despite empirical evidence suggesting a positive impact of regular physical activities on learning and memory. Reports show that their exam performance is just above the passing marks and that they find it hard to look for jobs. Thus, this research investigates psychosocial factors that might play a significant role in academic achievements in the context of a Malaysian sports school. This study adopted the predictive correlational research design and was conducted on 282 secondary school-aged student-athletes. Participants were selected using stratified random sampling to make sure that all age groups were covered. A series of Pearson's Correlation Coefficients were performed to determine the relationships between psychosocial factors (mindsets, perceived social support, and achievement motivation) with academic achievements in four core subjects – Bahasa Melayu, English, Mathematics, and Science and engagement (cognitive and affective). Multiple linear regressions were also carried out to investigate the significant psychosocial predictors of academic achievement. Despite previous studies that found strong relationships between psychosocial factors and student academic performance, the current research found that the psychosocial factors examined did not significantly predict academic achievement of student-athletes. Motivation seems to be the only factor that has a significant relationship with academic achievement in all four core subjects. Based on the data, the student-athletes in general have growth mindsets in both academic and sports, low to medium perceived social supports, and that male student-athletes have higher amotivation levels. Intrinsic and extrinsic motivation have positive correlations with language subjects and negative correlations with amotivation. Intrinsic motivation towards accomplishment was an additional significant predictor for the Science subject. Finally, the mediation analyses show five subcategories of motivation – intrinsic motivation to know, towards accomplishment, to experience stimulation, extrinsic motivation identified, and amotivation – to be mediated significantly by affective engagement with only the language subjects, especially English. In sum, the main findings of this study suggest that motivation plays a significant role in affecting student outcomes in the four core subjects, but especially on language subjects, shedding new light on issues pertaining to student-athletes' academic achievement. This study has demonstrated a clear implication that motivation is the only psychosocial factor that plays an integral part in improving studentathletes’ academic achievement in the current sample thus schools should prioritize addressing the lack of this fundamental driving force that energizes and directs student behaviour toward achievement over other enrichment programs.